Rogueing or Rescuing? A Potential New Management Approach for Roses Infected with Rose Rosette Virus - Caleb Paslay; Akhtar Ali (Viruses)
Roses (Rosa spp.) are among the most economically and culturally significant flowering plants worldwide. However, rose cultivation faces a critical threat from rose rosette disease (RRD), which is caused by Emaravirus rosae (rose rosette virus, RRV), a negative-sense RNA virus transmitted by the eriophyid mite Phyllocoptes fructiphilus. Current RRD management strategies mainly depend on the complete removal (rogueing) of symptomatic plants, which are effective but adds high economic and aesthetic costs. During our field and laboratory observations from 2023 to 2024, we documented that RRV often remains localized to a single cane for extended periods of time (up to 80 days) in one variety before systemic spread to other canes of the same plant. This discovery supports a proposed “rescue hypothesis”, suggesting that early pruning of symptomatic canes may prevent full-plant infection and serve as a viable alternative to rogueing under specific conditions. While preliminary, our findings offer a potentially cost-effective, less destructive management strategy. However, further research is needed to validate this hypothesis and inform integrated disease management practices are established for effective control of RRD.